2011
DOI: 10.3176/earth.2011.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phytoplankton pigments in water and surface sediments of a large shallow lake

Abstract: Our aim was to find out to which extent fossil phytoplankton pigments in the large shallow and turbid Lake Võrtsjärv carry information on the history of phytoplankton communities. For this purpose we examined how the changes in the pigment composition of surface sediments follow their changes in the water column. Depth-integrated lake water and surface sediment samples were collected weekly in May–October 2007. Considering cyanobacterial and diatom dominance in phytoplankton, we analysed fucoxanthin, diadinoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The increased concentrations of particulate and dissolved matters raises the respiration rate causing a decline in NEP. As the fresh sediment in Võrtsjärv still contains intact algal cells and degradation products of algal pigments (Freiberg et al, 2011), the observed increase of Chl a towards autumn is partially caused by resuspension and cannot be fully be attributed to algal growth and the reduction of zooplankton grazing pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The increased concentrations of particulate and dissolved matters raises the respiration rate causing a decline in NEP. As the fresh sediment in Võrtsjärv still contains intact algal cells and degradation products of algal pigments (Freiberg et al, 2011), the observed increase of Chl a towards autumn is partially caused by resuspension and cannot be fully be attributed to algal growth and the reduction of zooplankton grazing pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The weak correlation in our study could be caused by low counting precision of this minority group but also by errors in quantification of minor pigments (such as diatoxanthin in case of chrysophytes) which are shared by several phytoplankton classes and thus may contribute to the discrepancies [ 22 ]. Diatoxanthin can also interconvert with diadinoxanthin as was shown in Freiberg et al [ 52 ] that makes the pigment-based chemotaxonomic assessment of chrysophytes and dinoflagellates more difficult. Still it is likely that a separate intercalibration exercise based on high precision counts of the minority groups might yield more consistent results and that the high sensitivity of the CHEMTAX method could prove one of its main advantages lowering the uncertainty of the minority group biomass estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The time of extraction varied from several minutes 6,18,29 to several hours 4,7,26 and even overnight. 5,11,16,17 However, the influence on extraction efficiency of freeze-drying prior to extraction is not clear. In the case of freeze-dried sediments a 5-10 % content of water was recommended to improve extraction of polar compounds, 4,30 but some authors used acetone for extracting freeze-dried material.…”
Section: Resultsmentioning
confidence: 99%